The Speed of Earnings Responses to Taxation and the Role of Firm Labor Demand - Gudgeon, Matthew; Trenkle, Simon (Journal of Labor Economics, 2024)
This paper studies the speed at which workers’ pretax earnings respond to tax changes along the intensive margin. We do so in the context of Germany, where a large notch in the tax schedule induces sharp bunching in the earnings distribution. We analyze earnings responses to two policy reforms that shift this notch outward and find clear evidence that frictions delay the earnings responses of more than 38% of workers. We propose that heterogeneity in firm labor demand plays a key role in generating the observed differences in the speed of workers’ earnings responses and provide supporting evidence.